KARAKTERISTIK PASIEN TUBERCULOSIS PARU DEWASA DI PUSKESMAS LUBUK BUAYA KOTA PADANG TAHUN 2024 - Laila Kurnia Raisa; Rosmaini Rosmaini; Zukhri Zainun (Yayasan Nusantara Hasana Berdikari, 2026)
Pulmonary tuberculosis, a chronic, infectious disease affecting the lung parenchyma, is caused by the bacterium Mycobacterium tuberculosis and spreads from person to person through the air. Tuberculosis is among the top 10 causes of death worldwide, increasing annually. To determine the characteristics of adult pulmonary tuberculosis patients at the Lubuk Buaya Community Health Center in Padang City in 2024, the study was conducted from February to July 2025. This descriptive, observational study involved 80 samples from all pulmonary tuberculosis patients, using a total sampling technique. The characteristics of adult pulmonary tuberculosis patients at the Lubuk Buaya Community Health Center in Padang City in 2024 were mostly based on age, 24 people (30.00%), male gender 57 people (71.25%), no history of diabetes mellitus 55 people (68.8%), negative history of HIV 79 people (88.7%), type of diagnosis was clinical bacteriological 73 people (91.3%), category 1 OAT therapy 80 people (100.0%) and the final outcome of treatment was mostly cured 78 people (97.5%). The characteristics of adult pulmonary tuberculosis patients at the Lubuk Buaya Community Health Center in Padang City in 2024 were mostly aged 18-25 years, male, type of diagnosis bacteriological, no history of diabetes, HIV negative status, category 1 OAT therapy and the final outcome of treatment was cured.